Inclusion complexes of the steroid hormones 17β-estradiol and progesterone with β- and γ-cyclodextrin hosts: syntheses, X-ray structures, thermal analyses and API solubility enhancements - Vicatos, Alexios I.; Hoossen, Zakiena; Caira, Mino R. (Beilstein Journal of Organic Chemistry, 2022)
Overcoming the challenges of poor aqueous solubility of active pharmaceutical ingredients (APIs) is necessary to render them bioavailable. This study addresses the poor solubility of two potent steroid hormones, 17β-estradiol (BES) and progesterone (PRO), via their complexation with two water-soluble native cyclodextrins (CDs) namely β-CD and γ-CD. The hydrated inclusion complexes β-CD·BES, β-CD·PRO, γ-CD·BES and γ-CD·PRO were prepared via kneading and co-precipitation, and 1H NMR spectroscopic analysis of solutions of their pure complex crystals yielded the host–guest stoichiometries 2:1, 2:1, 1:1 and 3:2, respectively. Both powder X-ray diffraction (PXRD) and single-crystal X-ray diffraction (SCXRD) were employed for focused studies of the isostructurality of the CD complexes with known complexes and structural elucidation of the new complexes, respectively. SCXRD analyses of β-CD·BES, β-CD·PRO and γ-CD·PRO at 100(2) K yielded the first crystal structures of CD complexes containing the hormones BES and PRO, while the complex γ-CD·BES was readily shown to be isostructural with γ-CD·PRO by PXRD. Severe disorder of the encapsulated steroid molecules in the respective channels of the CD molecular assemblies was evident, however, preventing their modelling, but combination of the host–guest stoichiometries and water contents of the four hydrated inclusion complexes enabled accurate assignment of the chemical formulae of these ternary systems. Predicted electron counts for the complexed molecules BES and PRO correlated reasonably well with the complex compositions indicated by 1H NMR spectroscopy. Subsequent measurements of the aqueous solubilities of the four complexes confirmed significant solubility improvements effected by encapsulation of the steroids within the CDs, yielding solubility enhancement factors for BES and PRO in the approximate range 5–20.
Keywords: cyclodextrin; complexation; 17β-estradiol; progesterone; solubility; X-ray diffraction